Narrating the stories of leaked data: The changing role of journalists after Wikileaks and Snowden. (October 2017) - Landert, Daniela; Miscione, Gianluca
Abstract: Traditionally, investigative journalists had a gatekeeping role between their confidential sources of information and the public sphere. Over the last two decades and with the arrival of new media, this role has been undergoing changes. Recent cases of whistleblowing, such as WikiLeaks and Snowden, illustrate how contemporary media allow individuals to release data directly to the global audience. This raises the question of how recent leaks affect how journalists operate. In this study we compare how The Guardian covered two cases of whistleblowing which are commonly referred to as WikiLeaks and Snowden. We analyze how access to leaked data is provided or facilitated on The Guardian website, how readers are invited to interact with these data and how journalists present their own activities. A qualitative analysis of the leading articles further shows how the stories are framed and how much prominence is given to the data and the various actors. The results show how the roles of journalists shift from gatekeeping to data management, interpretation, contextualisation and narration. Journalists may no longer be needed to publish leaked data but they are still needed to tell the stories of leaked data.